2012
DOI: 10.5301/jva.5000105
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Stent Fracture and Migration to Pulmonary Artery during Arteriovenous Shunt Thrombectomy

Abstract: Although there is no consensus for the management of endovascular stents that have migrated to the pulmonary arteries, stent retrieval may be necessary in cases where arterial flow is compromised or heavy clot burden is a concern. Moreover, steps toward prevention of stent fracture and migration should be considered in order to preclude such occurrences--avoidance of puncturing the stent for hemodialysis access, discontinuation of use of the Arrow-Trerotola device through or near stents, and consideration of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…femoral vein CVC) must be considered for those patients. Ho et al 16 describe stent fracture and migration following recurring thrombectomies.…”
Section: Discussionmentioning
confidence: 99%
“…femoral vein CVC) must be considered for those patients. Ho et al 16 describe stent fracture and migration following recurring thrombectomies.…”
Section: Discussionmentioning
confidence: 99%
“…These cases may lead to embolization, infection, cardiac damage, or even death. [ 8 11 ] The common types of these FB are needles, [ 5 ] intravenous cannulas, [ 4 ] guidewires, [ 12 ] stents, [ 13 ] inferior vena cava filter struts, [ 14 ] and other objects (see Table 1 ). [ 6 , 7 , 15 , 16 , 17 19 ] However, being a rare pathogenic factor, the more unconventional non-iatrogenic FB often requires more extensive treatment and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective image review suggested that the stent may have migrated within 2 months after its insertion; stent migration was identified late because serious acute complications, such as cardiogenic shock, RV rupture, TV injury, and arrhythmia, did not occur. Although stent migration is a rare complication of stent placement that can occur at the time of placement or later, a vascular stent inserted into a central vein stenotic lesion should be periodically monitored for migration 2)…”
mentioning
confidence: 99%